Representation of Feminism in Bene Gesserit Members in Dune Film : Part Two (Semiotic Analysis of John Fiske) - Risvandi, Achmad Rian; Fikri, M. Andi (Universitas Muhammadiyah Sidoarjo, 2024)
Film is one form of mass communication media in the form of moving images that always influences and shapes society through the messages behind it. The messages and values contained in films not only provide entertainment but also education, giving people an understanding of the storyline, meaning, and messages within. One such film is Dune: Part Two, the third fictional adaptation of the novel by Frank Herbert (1965), which tells the story of human life in the future. In this film, female characters are depicted as active subjects of the narrative, conveying messages of feminism. The topic of feminism attracts the attention of researchers as it strives for justice and liberation from the oppression of women. The purpose of this research is to understand the semiotic code meaning regarding the representation of feminism in Dune: Part Two. To achieve the research objectives, the researcher employs a qualitative approach using John Fiske's semiotic analysis, based on three categories of feminism: reality, representation, and ideology. The results of the study show feminist values in the reality category through codes of appearance, makeup, costumes, speech, body movements, and expressions. In the representation category, feminist values are shown through camera codes, characters, and conflicts. Meanwhile, in the ideology category, feminist values are represented through specific dialogues and attitudes that reflect feminist behavior.